Improving instruction through supervision, evaluation, and professional development - DiPaola, Michael F., 1947- (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
In this second edition of Improving Instruction Through Supervision, Evaluation, and Professional Development we've maintained the conceptual framework while updating sections to provide the most recent research on instructional strategies that have the most promise of helping all students learn. Modifications of the law resulting from the reauthorization of the 50-year-old Elementary and Secondary Education Act--Every Student Succeeds Act (ESSA) (2015)--and their implication for practice are embedded throughout this new edition. Updated data collection tools for classroom observations are also provided. We included a link to a website that contains all the observation tools in electronic format so that observers can have the opportunity to collect data on a tablet or laptop, save the observation data as a PDF file and e-mail those data to the teacher observed.This new edition recognizes the reality that all principals are responsible for supervision, evaluation, and professional development of their teachers--tasks that are neither simple nor without conflict. The primary audience of this text is aspiring and practicing principals. We hope to help them understand both the theory and practice of supervision, evaluation, and professional development. However, observing instruction, collecting data for reflection, and having conversations about teaching, are not the sole provinces of principals. Master teachers, teacher leaders, and teacher colleagues can also benefit from the supervisory sections of the book, especially the chapters on high-quality instruction, improving instruction, and the classroom data collecting tools.The book provides numerous tools specifically designed to collect a variety of data in classrooms to improve instruction. Embedded in each chapter are exercises to apply Theory into Practice by responding to a set of questions posed by the key issues of the chapter. After the explication and illustration of the key concepts and principles of the chapter, actual Instructional Leadership Challenges as described by a successful practicing principal for reflection and analysis.